The Use of Facial Recognition Technologies by Law Enforcement Authorities in the US and the EU: Towards a Convergence on Regulation? - Tracol, Xavier (Technology and Regulation, 2025)
Law enforcement authorities have been using facial recognition technologies for many years in both the US and the EU. Some US legislators adopted bans and/or moratoriums whilst other US legislators adopted nuanced regulations about such use. The EU legislature considered adopting a ban of the use of live or real-time facial recognition technologies by law enforcement authorities in publicly accessible spaces. The EU legislature however ended up adopting a partial ban which provides for many broad exceptions. In this context, the US and the EU share a common interest in sharing experience about regulating the use of facial recognition technologies by law enforcement authorities.